17.6%-Efficient radial junction solar cells using silicon nano/micro hybrid structures. Issue 30 (13th July 2016) - Lee, Kangmin; Hwang, Inchan; Kim, Namwoo; Choi, Deokjae; Um, Han-Don; Kim, Seungchul; Seo, Kwanyong
Abstract : We developed a unique nano- and microwire hybrid structure by selectively modifying only the tops of microwires for highly efficient radial junction solar cells. Abstract : We developed a unique nano- and microwire hybrid structure by selectively modifying only the tops of microwires using metal-assisted chemical etching. The proposed nano/micro hybrid structure not only minimizes surface recombination but also absorbs 97% of incident light under AM 1.5G illumination, demonstrating outstanding light absorption compared to that of planar (59%) and microwire arrays (85%). The proposed hybrid solar cells with an area of 1 cm 2 exhibit power conversion efficiencies ( E ff ) of up to 17.6% under AM 1.5G illumination. In particular, the solar cells show a high short-circuit current density ( J sc ) of 39.5 mA cm −2 because of the high light-absorbing characteristics of the nanostructures. This corresponds to an approximately 61.5% and 16.5% increase in efficiency compared to that of a planar silicon solar cell ( E ff = 10.9%) and a microwire solar cell ( E ff = 15.1%), respectively. Therefore, we expect the proposed hybrid structure to become a foundational technology for the development of highly efficient radial junction solar cells.